METHODS OF PRESENTATION OF THE BASIC CONCEPTS TO STUDENTS WHEN PERFORMING LABORATORY WORK IN PHYSICS IN TECHNICAL UNIVERSITIE: METHODS OF PRESENTATION OF THE BASIC CONCEPTS TO STUDENTS WHEN PERFORMING LABORATORY WORK IN PHYSICS IN TECHNICAL UNIVERSITIES - Kozibay А.Қ.; Zhanbekova Г.И.; Akhmetkalieva Г.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this article, when performing laboratory work with electricity and magnetism general physics in technical universities students are encouraged to explain the operation procedure and the internal structure of the electrical appliances to expand the measurement range of the ammeter and voltmeter and to determine the values of parts on the scale. The article deals with the development and justification of methods of laboratory work in physics with elements of research aimed at the implementation of criteria-context method of training. Here, the methodology of our analytical work is the integration of scientific theory and professional sphere in the process of teaching students to use scientific elements from deductive scientific data collection and laboratory work. Methodological methods of laboratory work in technical universities, their value for future specialists are explained.